Creditor concentration: an empirical investigation - Steven Ongena; Günseli Tümer-Alkan; Natalja von Westernhagen (Deutsche Bundesbank, 2007)
Most of the literature addressing multiple banking assumes equal financing shares. However, unequal, concentrated or asymmetric bank borrowing is widespread. This paper investigates the determinants of creditor concentration for German firms using a comprehensive bank-firm level dataset for the time period between 1993 and 2003. We document that lending is very often concentrated and, consequently, that relationship lending is important, not only for the small firms but also for the larger firms in our sample. However, we also find that risky, illiquid, large and leveraged firms spread their borrowing more evenly between multiple lenders. On the other hand, the degree of concentration increases with the profitability of the relationship lender. Relationship lending may spur financing provided by other banks, especially if the relationship lender is a public sector bank and if the other banks are large or do not have to tie up additional funds in capital.
Keywords: G33; G32; G21; 330; bank relationships; asymmetric financing; banking competition; Unternehmen; Kredit; Lieferanten-Kunden-Beziehung; Gläubiger; Hausbank; Deutschland